Keo, Chetra (audio interview #5 of 5) - Keo, Chetra; Pierce, Mark, interviewer
<>INTERVIEW DESCRIPTION<> - This is the last of five interviews with conducted over a three month period with Chetra Keo, a friend of the interviewer. In contrast to the previous interviews, this one is shorter. As before, the interview was conducted in Keo's room, late at night. 1/20/1990